Current Insights into Animal Models of Graves’ Disease and Orbitopathy - Wiesweg, B.; Johnson, K.T. M.; Eckstein, A. K.; Berchner-Pfannschmidt, U. (Hormone and Metabolic Research, 2013)
Graves’ disease (GD) is a systemic autoimmune disease that is characterized by hyperthyroidism, orbitopathy and in rare cases dermopathy. Graves’ orbitopathy (GO) is an inflammatory disease of eye and orbit which occurs in about 30–60% of patients. Hyperthyroidism occurs due to the presence of stimulating TSHR-autoantibodies (TRAbs) leading to increased serum levels of thyroid hormones. Attempts to induce Graves’ disease in mice by immunization against the hTSHR or its variants have resulted in production of TRAbs that stimulate thyroid follicular cells to increase thyroid hormone secretion. Graves’ like orbital changes, such as inflammation, adipogenesis and muscle fibrosis are more difficult to induce. In this review we summarize different methods used to induce murine Graves’-like disease and their impact on murine orbits.
Keywords: murine models; autoimmunity; TSHR-antibodies; genetic immunization; mouse orbit